AIR DEFENCE IDENTIFICATION ZONE: UPAYA MENJAGA KEDAULATAN WILAYAH UDARA INDONESIA - Afrizal Razqi (Media Keadilan: Jurnal Ilmu Hukum, 2021)
ABSTRACTAir is an inseparable part of a country, a country's sovereignty over land and sea also means sovereignty over airspace. As an international community, it is only natural that Indonesia's airspace is used for the common interest of supporting population mobility and economic improvement. However, Indonesian sovereignty over airspace is still being violated by foreign aircraft. Air Defence Identification Zone (ADIZ) is a zone for identification of foreign aircraft before entering the airspace. The determination of ADIZ Indonesia needs to be accompanied by various preparations including improving positive laws regarding airspace security, completing air defense system infrastructure, and building an understanding of the concept of ADIZ Indonesia with neighboring countries directly bordering Indonesia. This paper uses a normative legal research method using a descriptive analysis approach, a legal material search technique uses a secondary data source obtained through a literature study, and a study analysis uses qualitative analysis. The results of the writing show that there are legal gaps and gaps in the determination of administrative sanctions fines, the lack of the number of radars belonging to the Indonesian Air Force under the National Defense Force in protecting Indonesian airspace, and the heavy-duty of the Ministry of Foreign Affairs to build the trust of neighboring countries amid the dynamics of the South China Sea territorial conflict if the government determines ADIZ Indonesia.Keywords: Airspace; Sovereignty; ADIZ. ABSTRAKUdara merupakan bagian yang tidak terpisahkan dari suatu negara, kedaulatan suatu negara akan daratan dan lautan juga berarti kedaulatan akan wilayah udara. Sebagai masyarakat Internasional, sudah sewajarnya wilayah udara Indonesia dimanfaatkan untuk kepentingan bersama guna mendukung mobilitas penduduk sampai peningkatan ekonomi. Namun kedaulatan Indonesia akan wilayah udara masih marak dilanggar oleh pesawat udara asing. Air Defence Identification Zone (ADIZ) merupakan zona identifikasi pesawat udara asing sebelum memasuki wilayah udara. Penetapan ADIZ Indonesia perlu dibarengi dengan pelbagai kesiapan meliputi penyempurnaan hukum positif mengenai pengamanan wilayah udara, melengkapi infrastruktur sistem pertahanan udara, dan membangun kesepahaman konsep ADIZ Indonesia dengan negara tetangga yang berbatasan langsung dengan Indonesia. Menggunakan metode penelitian hukum normatif dengan menggunakan pendekatan deskriptif analisis. Teknik penelusuran bahan hukum menggunakan sumber data sekunder yang didapat melalui studi kepustakaan. Analisis kajian menggunakan analisis kualitatif. Hasil penulisan menunjukan bahwa ada celah dan kekosongan hukum dalam penetapan denda sanksi administratif, kurangnya jumlah radar milik TNI AU dibawah Kohanudnas dalam melindungi wilayah udara Indonesia, dan tugas berat Kementerian Luar Negeri untuk membangun kepercayaan negara tetangga ditengah dinamika konflik teritorial Laut China Selatan apabila pemerintah menetapkan ADIZ Indonesia.